2022
DOI: 10.1088/1755-1315/1022/1/012078
|View full text |Cite
|
Sign up to set email alerts
|

Potential Alternative Evapotranspiration Estimation Methods for Batu Pahat Climatic Condition: A Quantitative Comparison

Abstract: Urbanisation had replaced the vegetation and soil cover, increasing heat retention by reducing the benefits of natural cooling mechanisms provided by evapotranspiration. The objective of this study is to investigate the potential of the alternative estimation performance for selected evapotranspiration (ET) methods for Batu Pahat station; for further prediction on the changes of future climatic parameters. Since the data is limited, ET0 estimation using temperature-based used are the Thornthwaite, Blaney-Cridd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
0
0
Order By: Relevance
“…La combinaison des moyennes des températures et des précipitations dans le diagramme ombro-thermique de Bagnouls-Gaussen permet un premier dépistage de sous-ensembles basés, à ce niveau, sur l'importance de la saison sèche dans le domaine étudié. Le diagramme ombro-thermique établi montre l'importance des saisons sèches et humides en durée et en intensité : quand la courbe de températures passe au-dessus de celle de précipitations, la période est sèche, dans le cas contraire la période est humide (Science, 2022).…”
Section: Résultats Et Discussionunclassified
“…La combinaison des moyennes des températures et des précipitations dans le diagramme ombro-thermique de Bagnouls-Gaussen permet un premier dépistage de sous-ensembles basés, à ce niveau, sur l'importance de la saison sèche dans le domaine étudié. Le diagramme ombro-thermique établi montre l'importance des saisons sèches et humides en durée et en intensité : quand la courbe de températures passe au-dessus de celle de précipitations, la période est sèche, dans le cas contraire la période est humide (Science, 2022).…”
Section: Résultats Et Discussionunclassified
“…Moreover, study in Kluang, Johor, which is near to Batu Pahat, had indicated an extreme temperature trend for the region of the Peninsular Malaysia, where it demonstrated that the majority of the extreme temperature indices for all stations have significantly higher trends [5]. The fluctuated mean temperature with a positive trendline had also demonstrated that the temperature of Batu Pahat is gradually increasing [6].…”
Section: Introductionmentioning
confidence: 98%